HUBUNGAN PENGETAHUAN IBU TENTANG VARIASI MAKANAN DENGAN STATUS GIZI PADA BALITA DI WILAYAH KERJA PUSKESMAS MANDIANGIN KOTA BUKITTINGGI TAHUN 2015 - Yelni, Afrida; Mandasari, Reski (LPPM Universitas Prima Nusantara Bukittinggi, 2017)
American union in 2006 more than 4 million people have constipation complaint often until it reaches a frequency of 2%. These constipation sufferers complain most are women. Children and adults over the age of 65 years old women. Pregnant women also often complain of constipation is approximately 2,5 million people who visit the doctor each year, the factor that causes constipation are lack of food that contains fiber. The title of this research is the relationship of consumption fe tablet to constipation in pregnant women in the Sikabu district, Solok, Gantiang district health centers Singgalang flat ground in 2014. This study was analytical ( cross-sectional) with primary and secondary using the obtained by measuring the guided observation and interviews using a checklist sheet. it sample are 34 pregnant women. This study was conducted on 16 and 19 March 2014 sampling technique in the total population (all respondents were a sample). With univariate analysis and bivariate processing is done by way of computerization and chi-square test. The results of the study showed that majority who have constipation as much as 25 respondents ( 73 % ), while respondents were less constipated 1 respondents ( 3 % ). So the value of p < 0.05 means that the results of this study are a significant correlation of consumption Relations FE tablet with the incidence of constipation in pregnant women. It is expected to further improve the education of health workers on the tablet consumption in the pregnant mother and fe tablet is expected to respondents to better understand how where do I take tablets fe.